Determinants of individuals' entrepreneurial intentions: a gender-comparative study. Issue 4 (8th August 2016) - Arshad, Muhammad; Farooq, Omer; Sultana, Naheed; Farooq, Mariam
Abstract : Purpose: The purpose of this paper is to examine the differentiated effects of entrepreneurial self-efficacy and social norms on individuals' entrepreneurial intentions (EIs), through the mediation of attitude toward entrepreneurship, by integrating the framework of gender schema theory with the theory of planned behavior. The authors posit that different factors stimulate the EIs of males and females, through attitude toward entrepreneurship, in developing countries. Design/methodology/approach: Data are collected from graduating students of South Asia's largest university. Structural equation modeling is used for model testing. Findings: The results show that perceived entrepreneurial self-efficacy has a greater effect on the attitude of males toward entrepreneurship than on the attitude of females, but perceived social norms have a greater effect on female attitude toward entrepreneurship. Attitude toward entrepreneurship has a positive impact on EIs. Originality/value: This is the first study of its nature which demonstrates that the EIs of males and females are induced by different factors. Where the social norms are the major factors in determining the EIs of the females, self-efficacy plays a vital role in predicting the EIs of their male counterparts. This study also attempts to clarify the relationship between self-efficacy, social norms, and EIs by positing entrepreneurial attitude as mediator. Moreover, it brings a fresh perspective through its setting in South Asia. By testing a model in the cultural setting of a developing country, this study differentiates the research from that conducted in the developed world.